Further integrating social context into comparative and environmental physiology - Killen, Shaun S.; Cortese, Daphne; Cotgrove, Lucy; Chrétien, Emmanuelle; Christensen, Emil; Crespel, Amélie; Jolles, Jolle; Pineda, Mar; Tiddy, Izzy C.; Fu, Cheng; Kochhann, Daiani; McKenzie, David J.; et al. (Company of Biologists, 2026)
Environmental factors such as temperature and oxygen are well-established modulators of animal physiology, but the influence of social context remains under-integrated into comparative and environmental physiology. Although numerous studies across behavioural, ecological and biomedical fields show that social interactions alter metabolic, hormonal, immune and stress-related traits, these insights are not routinely incorporated into physiological study design or interpretation. Social effects arise through mechanisms such as isolation, dominance hierarchies, altered energy use and social buffering, and can amplify or dampen responses to abiotic stressors. Because metabolic and hormonal pathways regulate multiple physiological systems, socially induced shifts can cascade to affect cardiovascular, immune, neural, digestive, osmoregulatory and reproductive function over both acute and evolutionary time scales. Thus, overlooking social context places researchers at risk of taking two critical missteps in comparative and environmental physiology: (1) measuring animals under socially unrealistic or uncontrolled conditions, which can yield unrepresentative physiological estimates; and (2) extrapolating these findings to natural populations where trait expression is influenced by social dynamics that are absent from the experimental context. Together, these issues might bias estimates of physiological trait values, plasticity and heritability, and limit the ecological relevance and predictive power of physiological research. Here, we outline general strategies to incorporate social context into experimental design, including the use of emerging tools that allow physiological measurements in naturalistic social settings. Integration of social context, alongside abiotic drivers, will improve our capacity to predict organismal responses to environmental change through comparative physiological research.